FLORAE MALESIANAE PRECURSORES-VI Malpighiaceae malesianae novae - J. ARENES (Reinwardtia, 1954)
Six new species of Malpighiaceae are described,five of Hiptage Gaertn. and one of Aspidopterys Juss.A new subdivision of the genus Hiptage Gaertn.is proposed, with three new combinations for sections and two new names for subsections.